Filmes finos eletrocrômicos: simulação de processos difusionais. - Rodrigues, Marco Paulsen (2022)
The present work aims to study the physical and electrochemical properties relevant to the ion diffusion process in electrochromic phenomena, specifically in WO3 thin films. To complete this investigation, this thesis was divided into an experimental and a computational phase. The results of these steps were analyzed comparatively. The films were produced via the sol-gel process. Different speeds were used for immersion and withdrawal according to the dip-coating technique. The temperature of the heat treatment was also varied, aiming to study its influence. Then, for the electrochemical characterization of the samples, the techniques of cyclic voltammetry, chronocoulometry and chronoamperometry were used. The optical characterization, employing the UV-vis spectroscopy technique, was performed simultaneously with the chronopotentiometry technique. In this way, it was possible to obtain unprecedented results relating the electro-insertion of charges to the modification of optical properties in electrochromic films. As for the morphological characterizations, the functional groups present in the samples were identified by the Fourier transform infrared spectroscopy technique. To infer the crystalline structure of the films, the x-ray diffraction technique was used. To study its superficial characteristics, the technique of atomic force microscopy was applied. Regarding the theoretical and computational sphere, for the first time in the literature, two new mathematical models for the analytical solution of the problem of chemical diffusion with diffusion coefficient dependent on position or time were presented. Both models and the computational code were then validated through comparison with experimental results. After proving their efficacy, the computational results served as a basis to explain the effect of different physical and electrochemical properties, supporting guidelines aimed at improving the performance of electrochromic devices. It is therefore expected that a new and improved understanding of the diffusion of lithium ions will be provided, promoting a positive impact with the potential to be extended to the study of different materials and devices, such as batteries and solar cells.